2020
DOI: 10.1177/0267659120971998
|View full text |Cite
|
Sign up to set email alerts
|

One-year experience of bedside percutaneous VA-ECMO decannulation in a high-ECMO-volume center in Hong Kong

Abstract: Background: When veno-arterial extracorporeal membrane oxygenation (VA-ECMO) support can be terminated, open repair of arteriotomy wounds in operating theaters is the standard of practice. Comparable outcomes by percutaneous decannulation using different closure devices have been reported. However, transport of the critically- ill, man-power and timeslots of operating theaters could be saved if decannulation was performed at bedside. Method: Bedside percutaneous arteriotomy wound closure became our default met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…However, site infection after cannula removal was uncommon (2.0%) in the preclosure group of our cohort and this rate was comparable to those demonstrated in postclosure following decannulation of VA-ECMO. 4,6,7 Further, in a previous study of the use of the preclosure technique in elective peripheral VA-ECMO before lung transplantation, similarly low rates of site infections were noted. 14 Historically, it has been typical to perform surgical vascular repair with exposure and repair of the common femoral artery at the time of decannulation from VA-ECMO.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…However, site infection after cannula removal was uncommon (2.0%) in the preclosure group of our cohort and this rate was comparable to those demonstrated in postclosure following decannulation of VA-ECMO. 4,6,7 Further, in a previous study of the use of the preclosure technique in elective peripheral VA-ECMO before lung transplantation, similarly low rates of site infections were noted. 14 Historically, it has been typical to perform surgical vascular repair with exposure and repair of the common femoral artery at the time of decannulation from VA-ECMO.…”
Section: Discussionmentioning
confidence: 81%
“…However, these techniques have not yet demonstrated improvements in clinical outcomes compared with surgical removal in this setting. [4][5][6][7][8] We suspect postclosure compared with preclosure may result in a more technically challenging VA-ECMO decannulation procedure and be prone to excessive blood loss when attempting to deploy the suture device after large-bore arterial access such as provided with VA-ECMO. It has been suggested that a possible…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the transport of critically ill patients on VA‐ECMO support is not without risk. Nowadays, an increasing number of centers have been practicing VA‐ECMO decannulation with different percutaneous closure devices 2–8 . This has resulted in relatively smaller wounds and fewer incidences of wound infections.…”
Section: Introductionmentioning
confidence: 99%